South American regional integration: Does it solely depend on the political convergence of its governments? - Apunte, Juan Francisco Camino (Ius Humani. Jornal do direito, 2024)
South American regional integration has been part of the political rhetoric of South America governments since the creation of the first regional organizations in 1969. However, in each subcontinent (Central America, South America, North America), they have established their own systems of integration and governance. In South America, except for the Andean Community of Nations and Mercosur, the rest have had an important political condition, and their strengthening and permanence are related to the political convergence between the governments of the region, because they have the constitutional attributions about the formulation and execution of foreign policy. This article analyzes through the QCA, whether it is indeed the political dimension that effectively explains the promotion, encouragement, and consolidation of regional integration in the subcontinent. For this purpose, two dimensions are proposed: the first is economic, measured through two variables such as complementarity and commercial interdependence, and the political dimension, measured through two variables: ideological distance and whether the promotion of integration is part of the constitutions of each country.